MiQ—A novel microRNA based diagnostic and prognostic tool for prostate cancer. Issue 12 (21st December 2012) - Larne, Olivia; Martens‐Uzunova, Elena; Hagman, Zandra; Edsjö, Anders; Lippolis, Giuseppe; den Berg, Mirella S. Vredenbregt‐van; Bjartell, Anders; Jenster, Guido; Ceder, Yvonne
Abstract Today, the majority of prostate tumors are detected at early stages with uncertain prognosis. Therefore, we set out to identify early predictive markers of prostate cancer with aggressive progression characteristics. We measured the expression of microRNAs (miRNA) using qRT‐PCR in formalin fixed and paraffin embedded prostatic tissue samples from a Swedish cohort of 49 patients with prostate cancer and 25 without cancer and found seven of 13 preselected miRNAs to discriminate between the two groups. Subsequently, four discriminatory miRNAs were combined to a quota, denoted the miRNA index quote (miQ); ((miR‐96‐5p × miR‐183‐5p)/(miR‐145‐5p × miR221‐5p)). The advantage of using a quote is increased discrimination, no need for house‐keepings, and most important it may be an advantage considering the heterogeneity of the disease. miQ was found to successfully predict diagnosis (p < 0.0001) with high accuracy (area under the curve, AUC = 0.931) that was verified in an independent Dutch cohort and three external cohorts, and significantly outperforming prostate‐specific antigen. Importantly, miQ also has prognostic power to predict aggressiveness of tumors (AUC = 0.895), metastatic statues (AUC = 0.827) and overall survival (p = 0.0013, Wilcoxon test HR = 6.5, median survival 2 vs. 5 years), verified in the Dutch cohort. In this preliminary study, we propose that miQ has potential to be used as a clinical tool for prostate cancer diagnosis and as a prognostic marker of disease progression.